2019
DOI: 10.1097/mcg.0000000000000902
|View full text |Cite
|
Sign up to set email alerts
|

Colonoscopy in Patients With Postmyocardial Infarction Gastrointestinal Bleeding

Abstract: Same admission colonoscopy performed for post-STEMI-C GIB was associated with lower mortality. However, despite increased incidence of GIB in these patients during the study period, a lower percentage of patients received colonoscopy. These results suggest that colonoscopy is safe but underutilized in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Performing endoscopy on patients with ACS is an area of concern for gastroenterologists. Sedation associated with endoscopy is a known stressor on the heart, however, has been shown to be safe following acute myocardial infarction in several studies [3,[15][16][17][18][19][20][21][22]. In the absence of upper GI bleeding, hematemesis, or hemodynamic instability, urgent endoscopy can safely be delayed [23].…”
Section: Discussionmentioning
confidence: 99%
“…Performing endoscopy on patients with ACS is an area of concern for gastroenterologists. Sedation associated with endoscopy is a known stressor on the heart, however, has been shown to be safe following acute myocardial infarction in several studies [3,[15][16][17][18][19][20][21][22]. In the absence of upper GI bleeding, hematemesis, or hemodynamic instability, urgent endoscopy can safely be delayed [23].…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, in our study, few patients underwent endoscopy. Although some studies have shown that endoscopic treatment of GIB in AMI patients is relatively safe,[ 27 28 29 ] clinicians usually choose relatively conservative therapy to avoid medical disputes. In addition, these patients usually received conservative treatment, so there were little coronary angiography data in the record.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, few patients underwent endoscopy in our study. Although some studies have pointed out that endoscopic treatment of GIB in patients with AMI is relatively safe (36)(37)(38), doctors usually choose relatively conservative treatment in order to avoid medical disputes. In addition, since we do not have the endoscopy results of these patients, the origin (lower and upper) of the GIB is unclear.…”
Section: Discussionmentioning
confidence: 99%